TP53-Activated lncRNA GHRLOS Regulates Cell Proliferation, Invasion, and Apoptosis of Non-Small Cell Lung Cancer by Modulating the miR-346/APC Axis - Ren, Ke; Sun, Jinghui; Liu, Lingling; Yang, Yuping; Li, Honghui; Wang, Zhichao; Deng, Jingzhu; Hou, Min; Qiu, Jia; Zhao, Wei (Frontiers in Oncology, 2021)
Non-small cell lung cancer (NSCLC) is the main type of lung cancer with high mortality worldwide. To improve NSCLC therapy, the exploration of molecular mechanisms involved in NSCLC progression and identification of their potential therapy targeting is important. Long noncoding RNAs (lncRNAs) have shown important roles in regulating various tumors progression, including NSCLC. We found lncRNA GHRLOS was decreased in NSCLC cell lines and tissues which correlated with poor prognosis of NSCLC patients. However, the role and underlying mechanism of lncRNA GHRLOS in NSCLC progression remains elusive. The expression of lncRNA GHRLOS was examined in NSCLC cell lines and biopsy specimens of patients with NSCLC by quantitative real time polymerase chain reaction (qRT-PCR). The effects of GHRLOS on proliferation, invasion and apoptosis of NSCLC cells were determined by both in vitro and in vivo experiments. The interaction between GHRLOS and TP53 was determined by dual-luciferase reporter assay and chromatin immunoprecipitation (ChIP) combined with qRT-PCR analysis. RNA immunoprecipitation (RIP) was conducted to validate the binding between GHRLOS and microRNA-346 (miR-346). Dual-luciferase reporter assays were also carried out to reveal the interaction between miR-346 and the 3’ untranslated region (3’UTR) of adenomatous polyposis coli (APC) mRNA. Our data demonstrated that overexpression of lncRNA GHRLOS suppressed cancer cell proliferation and invasion as well as promoted cell apoptosis by regulating the expression of CDK2, PCNA, E-cadherin, N-cadherin, Bax, and Bcl-2 in NSCLC cells. Moreover, lncRNA GHRLOS was upregulated by the binding of TP53 to the GHRLOS promoter. The binding target of lncRNA GHRLOS was identified to be miR-346. Impressively, overexpression of miR-346 promoted cell proliferation and invasion, as well as inhibited cell apoptosis. However, these effects can be blocked by overexpression of lncRNA GHRLOS both in vitro and in vivo. In summary, this study reveals lncRNA GHRLOS, upregulated by TP53, acts as a molecule sponge of miR-346 to cooperatively modulate expression of APC, a miR-346 target, and potentially inhibit NSCLC progression via TP53/lncRNA GHRLOS/miR-346/APC axis, which represents a novel pathway that could be useful in targeted therapy against NSCLC.